Effect of Polymerization Conditions on Thermal and Mechanical Properties of Ethylene/1-Butene Copolymer Made with Ziegler-Natta Catalysts - Mostafizur Rahaman; M. Anwar Parvez; J. B. P. Soares; I. A. Hussein (International Journal of Polymer Science)
The effect of polymerization conditions on thermal and mechanical properties of ethylene/1-butene copolymers synthesized through titanium-magnesium-supported Ziegler-Natta catalysts was studied. The increase in hydrogen pressure leads to a decrease in molecular weight (MW), storage modulus, and melting temperature. However, it yields an increase in molecular weight distribution (MWD), tan⁡δ, % crystallinity, tensile modulus, yield stress, and strain at break. The effects of ethylene pressure and polymerization temperature on the copolymer MW, MWD and thermal and mechanical properties have been investigated. However, the impacts of ethylene pressure and polymerization temperature on copolymer modulus, tensile strength, % crystallinity, crystallization peak temperature, yield stress, strain at break, and yield strain are marginal. The hydrogen pressure plays a major role in controlling the copolymer properties because it acts as an efficient chain transfer agent during polymerization reaction. The MW is the key parameter that influences flow activation energy. However, the other mechanical, dynamic mechanical, and thermal properties not only depend on MW but are also influenced by other parameters.